(untitled) (Journal of Engineering, 2025)
This study examines the behavior of fatigue crack propagation in aluminum alloy sheets used in aircraft wings, with a particular focus on critical angles of attack (AOA). The widely utilized aluminum alloys 2024-T3 and 7075-T6 were analyzed to determine the effects of varying AOAs, representing normal flight (5°) and takeoff/landing (10°) on crack growth rates. A comprehensive approach was adopted, integrating experimental testing, numerical simulations, and analytical modeling. Experimental methods included material characterization and multiaxial fatigue tests using an innovative apparatus. Numerical simulations conducted with ANSYS 2021 CFD evaluated stress distributions and crack propagation under different wind loads and AOA conditions. Analytical modeling applied the Paris-Erdogan equation and fracture mechanics principles to predict crack growth behavior. The results revealed that higher AOAs significantly accelerate crack growth in both alloys. Notably, AL2024-T3 demonstrated slower crack propagation than AL7075-T6, indicating superior fatigue resistance, especially at lower AOAs. The fracture growth rates were determined to be 0.005 mm/sec for AL2024-T3 and 0.009 mm/sec for AL7075-T6. These findings have important implications for aircraft design, maintenance, and material selection. They underscore the necessity of accounting for AOA-dependent fatigue behavior to improve the durability and safety of aircraft structures.